Матрица монодромии, свойства мультипликаторов для двухпараметрической задачи Дирака - Саакян, Г. Г.
Matrix o f monodromy and multipliers for Dirac's two-parameter problem with periodical Hermitians are being defined in this work. In theorem 1 concerning matrix, two properties are being proved. In theroem 2 and 3 the type and arrangement of multipliers for real and complex λ1,λ.2, are being determined.
Keywords: Матетатика